Post-treatment of refinery wastewater effluent using a combination of AOPs (H2O2 photolysis and catalytic wet peroxide oxidation) for possible water reuse. Comparison of low and medium pressure lamp performance. (15th March 2016) - Rueda-Márquez, J.J.; Levchuk, I.; Salcedo, I.; Acevedo-Merino, A.; Manzano, M.A.
Abstract: The main aim of this work was to study the feasibility of multi-barrier treatment (MBT) consisting of filtration, hydrogen peroxide photolysis (H2 O2 /UVC) and catalytic wet peroxide oxidation (CWPO) for post-treatment of petroleum refinery effluent. Also the possibility of water reuse or safe discharge was considered. The performance of MBT using medium (MP) and low (LP) pressure lamps was compared as well as operation and maintenance (O&M) cost. Decomposition of organic compounds was followed by means of gas chromatography–mass spectrometry (GC–MS), total organic carbon (TOC) and chemical oxygen demand (COD) analysis. After filtration step (25 μm) turbidity and concentration of suspended solids decreased by 92% and 80%, respectively. During H2 O2 /UVC process with LP lamp at optimal conditions (H2 O2 :TOC ratio 8 and UVC dose received by water 5.28 WUVC s cm −2 ) removal of phenolic compounds, TOC and COD was 100%, 52.3% and 84.3%, respectively. Complete elimination of phenolic compounds, 47.6% of TOC and 91% of COD was achieved during H2 O2 /UVC process with MP lamp at optimal conditions (H2 O2 :TOC ratio 5, UVC dose received by water 6.57 WUVC s cm −2 ). In order to compare performance of H2 O2 /UVC treatment with different experimental set up, the UVC dose required for removal of mg L −1 of COD was suggested as a parameter and successfully applied. The hydrophilicity of H2 O2 /UVC effluent significantly increased which in turn enhanced the oxidation of organic compounds during CWPO step. After H2 O2 /UVC treatment with LP and MP lamps residual H2 O2 concentration was 160 mg L −1 and 96.5 mg L −1, respectively. Remaining H2 O2 was fully consumed during subsequent CWPO step (6 and 3.5 min of contact time for LP and MP, respectively). Total TOC and COD removal after MBT was 94.7% and 92.2% (using LP lamp) and 89.6% and 95%, (using MP lamp), respectively. The O&M cost for MBT with LP lamp was estimated to be 0.44 € m −3 while with MP lamp it was nearly five times higher. Toxicity assessment was performed using two marine species ( Vibrio fischeri and Paracentrotus lividus sea-urchin) after each treatment step. The highest toxicity was attributed to H2 O2 /UVC effluent for both tested species. After MBT a drastic decrease of toxicity was achieved. Graphical abstract: Highlights: Degradation performance of H2 O2 /UVC was compared by UVC dose received by water. The O&M cost of H2 O2 /UVC step with MP lamp is five times higher than with LP lamp. The water toxicity was increased after H2 O2 /UVC step and reduced after CWPO. The water quality after Multi-Barrier Treatment suggests its suitability for reuse.